FUNGSI GREEN UNTUK PERSAMAAN DIFUSI-ADVEKSI DENGAN SYARAT BATAS DIRICHLET - Josua, Josua; Noviani, Evi; Fran, Fransiskus (PATTIMURA UNIVERSITY, 2020)
Diffusion-advection is the process of transportation of matter from one part of a system to another as a result of random molecular motions involving fluid transport processes in the form of mean flow or currents which are driven by gravity or pressure forces and in the form of horizontal motions. Mathematically, diffusion-advection equation can be written as where is concentration of material in the fluid, stands for the advection velocity, and for diffusion coefficient. In this paper, a solution is sought by using the Green’s function concept. The general solution for Green’s function that can be solved in two parts, namely, the principal solution and the regular solution. The principal solution is obtained by applying the Fourier transform to the variable which is denoted by and then calculate the inverse of its transform. A regular solution is obtained based on an inspection approach that is designed on a negative heat source.